2007
DOI: 10.21608/jpp.2007.220895
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF VARIETIES AND WEED CONTROL TREATMENTS ON WEEDS, GROWTH CHARACTERS, YIELD AND YIELD COMPONENTS OF PEANUT(Arachis hypogaea L.)

Abstract: The present study including two field experiments were carried out in sandy soil in Ismailiah Agriculture Research Station during 2004 and 2005 successive summer seasons. The first experiment laid in split plot design was aimed to study the response of two peanut varieties Giza 6 and Gregory and ten weed control treatments being (1) Pendimethalin at 850 g/fed (2) Pendimethalin at 850 g/fed + hand hoeing (3) oxyfluorfen at 125 g/fed (4) oxyfluorfen at 125 g/fed + hand hoeing (5) Butralin at 1200 g/fed (6) Butra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…The application of Amex at rate 1.5 L/feddan, Cougar at rate 2.0 L/feddan, Stomp extra at the rate of 1.5L/f eddan, (Bazagran at rate of 0.75 L/feddan+Fusilade super at rate 1.0 L/feddan) and hand hoeing twice decreased the braod-leaved weeds dry weight (g/m 2 ) by (74.7, 77.0, 77.6, 83.8 and 77.8%) in 2020 season and by (72.8, 73.7, 75.7, 86.1 and 77.2%) in 2021 season, respectively as compared with unweeded treatment (Table 6). These results were consistent with those obtained by Moshtohry et al (2007).…”
Section: Effects Of Weed Control Treatments On Dry Weight Of Broad-le...supporting
confidence: 93%
See 1 more Smart Citation
“…The application of Amex at rate 1.5 L/feddan, Cougar at rate 2.0 L/feddan, Stomp extra at the rate of 1.5L/f eddan, (Bazagran at rate of 0.75 L/feddan+Fusilade super at rate 1.0 L/feddan) and hand hoeing twice decreased the braod-leaved weeds dry weight (g/m 2 ) by (74.7, 77.0, 77.6, 83.8 and 77.8%) in 2020 season and by (72.8, 73.7, 75.7, 86.1 and 77.2%) in 2021 season, respectively as compared with unweeded treatment (Table 6). These results were consistent with those obtained by Moshtohry et al (2007).…”
Section: Effects Of Weed Control Treatments On Dry Weight Of Broad-le...supporting
confidence: 93%
“…Khozimy (2006) showed that fluazifop-p-butyl had a passable impact on the dry weights of narrow and total weeds at 45 days after planting, whereas clethodim had a higher ability to reduce dry weights of narrow and total weeds compared to other treatments. Moshtohry et al (2007) indicated that butralin was an alternative to oxyfluorfen and pendimethalin against annual weeds, whose dry weight fell by 85-92%. The dry weight of the grasses dropped by 84-99% when treated with clethodim or fluazifop-butyl.…”
Section: Introductionmentioning
confidence: 99%
“…Dengan demikian, pemenuhan kebutuhan kalium yang adekuat menjadi faktor penting dalam meningkatkan hasil dan kualitas produksi tanaman secara keseluruhan. Selain itu, kalium membantu memperkuat dinding sel tanaman sehingga hama dan penyakit lebih sulit menyerang tanaman, seperti polong dan biji kacang tanah (Setiawan et al, 2018).…”
Section: Pembahasanunclassified